A description of the skeletal morphology of Rana pyrenaica (Anura: Ranidae), with comments on functional morphology, ecological adaptation and relationships with other Iberian ranids - Blain, Hugues-Alexandre; Arribas, Oscar J. (Zootaxa, 2017)
Despite being described in 1993, the skeleton of Rana pyrenaica Serra-Cobo, 1993 has never been investigated. The present publication thus represents the first description of the osteology of the spring-dwelling Pyrenean small brown frog. Its specific status is osteologically supported by some discrete differences. When compared with other Iberian brown frogs, it shows a mosaic of characters that are difficult to interpret. However, according to ecomorphology, R. pyrenaica shares a robust skeleton morphology and various morphological traits with the more terrestrial Rana temporaria (Linnaeus, 1758), but also shares some more aquatic life osteological characters with the aquatic Rana iberica Boulenger, 1879. As well as increasing what is known about R. pyrenaica, this study also aims to facilitate the correct diagnosis of the species in fossil assemblages and its osteological identification as the prey of other vertebrates in trophic studies.